Beneficial utilization of waste heat for developing fly ash based geopolymer mortar - Vishal Ray; Kummari Sekhar; Narala Gangadhara Reddy; Bendadi Hanumantha Rao (Discover Civil Engineering)
Abstract Adoption of elevated temperature curing significantly limits the scalability of fly ash based geopolymer technology because it requires high energy and cost. Conversely, 60–70% of heat energy from electrostatic precipitators, which exits fly ash at ~ 150 °C, is released as a waste heat by a thermal power plant. This study aims to harness such waste heat for curing geopolymer mortar (GPM), which circumvents the need for conventional thermal energy, made with fly ash. To replicate the waste heat, both fly ash (to 150 °C) and pan mixture (to 50, 60, and 80 °C) are preheated. GPM cubes are cast with preheated fly ash by activating with alkaline activator solutions (AAS). A maximum strength of 24.35 MPa, which is 115.7% gain over ambient control (11.29 MPa at 27 °C), is accomplished at fly ash temperature of 150 °C, AAS to binder solids ratio of 0.5, pan temperature of 80 °C, and NaOH of 12 M. The results underscore a breakthrough in integrating waste heat to sustainable GPM production, specifically suitable for precast concrete applications.